The early modern period - Francisco Bethencourt (2015)
This History of Portugal has the advantage of presenting in one single volume a comprehensive vision of the past, from the foundation of the kingdom to contemporary history. It is not a history written by one single author, and thus follows a different approach from that of Oliveira Marques, who clearly stands as the previous most professional and efficient historian engaging with this genre. The decision was the right one: each of the three authors knows his period of specialization well.